On the Formal Interpretation of SysML Blocks Using a Safety Critical Case Study - Jacobs, Jaco; Simpson, Andrew (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2014)
The Systems Modeling Language (SysML) is a semi-formal, visual modelling language used in the specification and design of systems. In this paper, we describe how Communicating Sequential Processes (CSP) and its associated refinement checker, Failures Divergences Refinement (FDR), can be used in conjunction with SysML in a formal top-down approach to systems engineering. Typically, a system is composed from constituent systems or components using the concept of blocks. SysML allows two alternative interpretations with regards to the behaviour of the resulting composition. By making use of a process-algebraic formalism we are able to explore these interpretations more rigorously. A case study is used throughout to illuminate the concepts in an informal manner.